Teori Pendekatan Tafsir: Teologis, Ideologis Ke Kritis - Zainal Arif (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2017)
The development of Qur’anic interpretation can be categorized into three periods: classical, modern and contemporary. Each of these categories of interpretation has some of the typical characteristics that we describe in detail in the following article. Each of these categories also has movements from: mythological to idiological and critical. Now, in the map of Islamic thought, these three forms of interpretation (classical, modern and contemporary) also have their own supportive community. The classical supporters of the classical tafsir include the salaf al-shalihand the majority of Islamic societies, later known as the scripturalist, fundamental, and traditional Islamists. The support community of modern interpretation is among Muslim scholars who interact with many Western scholars. The community of contemporary commentators is Islamic-liberal-reformist, pluralist or substantial Islamist.